The Performance of Microalgae (Nannochloropsis sp., Tetraselmis sp. and Dunaliella sp.) on White Shrimp (Litopenaeus vannamei) Wastewater Cultivation Media - Muhammad Browijoyo Santanumurti; Santrika Khanza; Zaenal Abidin; Berta Putri; Siti Hudaidah (Department of Aquaculture, 2022)
Microalgae have an important role in supporting the development of aquaculture because it can be used as natural feed. However, its culture requires an expensive cost because of the nutrient media. To reduce the cost, the media can be replaced by using wastewater from white shrimp (Litopenaeus vannamei) culture. This research was aimed to find out the performance of microalgae (Nannochloropsis sp., Tetraselmis sp. and Dunaliella sp.) cultured on white shrimp wastewater. The performance was measured by the growth, density, and ability to reduce nitrate and phosphate. The experimental design used in this study was a Completely Randomized Design with three treatments and three replications. The treatments were A (Nannochloropsis sp. cultured in white shrimp wastewater), B (Tetraselmis sp. cultured in white shrimp wastewater), and C (Dunaliella sp. cultured in white shrimp wastewater). The density population of Nannochloropsis sp., Tetraselmis sp. and Dunaliella sp. were tested by ANOVA. ANOVA was used to assess the density population of Nannochloropsis sp., Tetraselmis sp., and Dunaliella sp., which was then followed by Duncan's test. The results showed that wastewater from white shrimp aquaculture could be used as a medium culture for Nannochloropsis sp., Tetraselmis sp. and Dunaliella sp. It also maintain good water parameter quality in media. Nannochloropsis sp. was the microalgae that produced the highest density of 34.5 x 104 ind/mL when cultured on waste water from white shrimp culture. Nannochloropsis sp. may also reduce nitrate and phosphate content by up to 76 and 61.37 percent, respectively.